Fungicide resistance and efficacy for control of Pyrenophora teres and Mycosphaerella graminicola on barley and wheat - Marzani, Qasim Abdulla (2011)
Barley net blotch (BNB) caused by Pyrenophora teres, and Septoria tritici blotch (STB) caused by Mycosphaerella graminicola, are destructive cereal diseases worldwide on barley and wheat respectively. Due to the lack of highly resistant cultivars, both diseases are widely controlled using fungicides. Systemic, site-specific modern fungicides have played an essential role in disease management in cereals. Triazole-based fungicides, which inhibit the C14 demethylation step in fungal ergosterol biosynthesis, known as demethylation inhibitors (DMIs) and strobilurins, known as quinine outside inhibitors (QoIs), which interfere with energy production in the fungal cell, by blocking electron transfer at site of quinone oxidation in the cytochrome bc1 complex, are two major site-specific systemic groups of fungicides, currently used to control cereal diseases. Multiple, consecutive and extensive use of these fungicides has led to the emergence of fungicide resistance in these plant pathogens. The existence of G143A and F129L mutations has been found to be associated with resistance of many plant pathogens to QoIs. However, in P. teres only F129L was found to confer insensitivity. The presence of an intron in several fungi (including rusts and P. teres) determines that it is impossible for the G143A mutation to survive and thus be selected for. Alterations in CYP51 gene in plant pathogens has also been found to be one of the major mechanisms resulting in reduced sensitivity towards DMIs. The aim of this research was to investigate the impact of the F129L mutation in isolates of P. teres, and mutations in the CYP51 gene in M. graminicola isolates on the activity of QoI and DMI fungicides respectively. Results revealed a high frequency of the F129L mutation within recent UK P. teres isolates. Furthermore, the common change (G143A) in cytochrome b was not found in P. teres strains. The results also showed a lack of any fitness penalty associated with the mutation. Bioassay tests indicated that inhibition of net blotch by QoIs was variable. Single QoI fungicides such as pyraclostrobin and picoxystrobin were found to be highly inhibitory whilst the efficacy of other QoIs was less pronounced. It has been found that efficacy of QoI fungicides varied amongst a population of isolates with the F129L mutation. This might suggest that some QoIs were compromised by the F129L mutation to some degree. However, the results obtained were in agreement with previous reports that the F129L mutation in the cytochrome b gene generates lower levels of resistance and was not as serious as that posed by the G143A mutation in other plant pathogens. In addition, fungicide mixtures, comprising QoIs and DMIs or the novel SDHI formulations, were found to have great efficacy in net blotch disease management. Sequence results of CYP51 gene fragment indicated existence of 15 alterations in recent UK and German isolates of M. graminicola. Some of these mutations, such as Y137F, were found to be rare whilst the I381V mutation was found to be increasing with time. However, investigations indicated a lack of phenotypic fitness penalties associated with these alterations. Apical germ tube growth measurement was found an effective method to assess in vitro activity of DMI fungicides against M. graminicola isolates. Based on bioassay studies, six categories within M. graminicola isolates were detected, showing different sensitivities to azole fungicides. In general, genotypes characterised S, R3+ and R4 were sensitive to most azole fungicides. The R3+ variant, however, showed less sensitivity to tebuconazole and prochloraz. In in vitro studies, the R5 variants, exhibited sensitivity to many DMIs but were less sensitive to prochloraz. This supporting the results obtained from in planta assays, where this genotype was found to be sensitive to tebuconazole but less sensitive to prochloraz. On the other hand, genotypes characterised R6a, R7 and R8, containing I381V mutation, were resistant to tebuconazole but sensitive to prochloraz. The latter variant, however, were more sensitive to prochloraz. It can be suggested from results obtained in this study that CYP51 alterations were differentially selected by different members of the azole class of fungicides. Q-PCR was also used to evaluate in planta fungicide activity on both diseases. The method indicated similar pattern to that observed in visual assessments. Detection of medium to high correlation values between both assessments confirmed the validity of q-PCR assessment. This suggests that q-PCR assays may serve as an alternative method for accurate assessment of the fungicide effects on cereal diseases. The method can be a valuable tool to evaluate disease occurrence in pathogens with a long latent period, such as M. graminicola, as q-PCR could readily detect the pathogen during the asymptomatic latent period.